Consumer Legal Protection Against The Purchase Of Legalized Land Lands Which Are Only Waiting For A Certificate Of Resolution - Sunardi, Sunardi; Rokhim, Abdul; Wiratamja, Novieyani (International Significance of Notary, 2025)
Abstract: What if the sale and purchase of plots of land that have been sold by the developer but there is still no splitting of the plot of land and it has already been sold, then the developer will make a letter of agreement which is legalized by a notary, can this be detrimental to the buyer and what is the certainty? the law is because the certificate is not certain to be in the name of the buyer, as well as the form of legal protection for the buyer. The problem formulation is as follows, What is the legal protection for consumers for the purchase of plots of land where the agreement is only legalized by a Notary? How is the strength of the agreement to buy and sell plots of land under the hands of the legalization by a Notary before the issuance of a split certificate according to the Civil Code and UUJN and. This research uses a normative research method with a statutory regulatory approach and a case approach, namely a case approach carried out by examining cases related to the legal issues faced, the results of research on Legal Protection for Buyers for Purchasing Land Plots Based on A private deed that is legalized by a notary is only so that there is certainty regarding the veracity of the signature contained in the private deed, and also certainty regarding the truth that the signature is truly the signature of the Parties; so that the seller immediately with a legalized private deed can receive payment for the plot of land before handing over, however, the buyer demands the implementation of the private agreement and the buyer gets a guarantee from the seller to guarantee that the object of the agreement is in control of the object being sold. safely and securely and guaranteeing against hidden defects, this is in accordance with article 1492 of the Civil Code. Meanwhile, protection for notaries must be in accordance with article 66 UUJN and notaries who legalize the deed below are only responsible for the authenticity of the signatures of the parties and the certainty of the legalization date. A private deed that is legalized by a Notary has the power of proof that is not the same as an authentic deed, because the signature contained in the private deed can be denied by the person signing and the party submitting it as evidence must prove its truth through other evidence or witnesses. And a private deed that is legalized does not qualify as an authentic deed, where one of the requirements for an authentic deed is that it is made by an authorized public official, while a private deed that is legalized by a notary is made by the parties.